Role of catecholamines in centrogenic cardiac arrhythmia induced by aconitine - Bhargava, K. P. (1969)
1. Injection of 20 μg of aconitine into the lateral ventricle of dogs anaesthetized with pentobarbitone regularly induced cardiac irregularities and hypertension. The cardiovascular changes appeared within 5 min and lasted for about 90 min. Tachyphylaxis to the aconitine-induced cardiovascular effects was observed. 2. The aconitine-induced arrhythmia and hypertension were centrogenic, for they were abolished or prevented by spinal transection (C(2)) or ganglionic blockade. 3. Bilateral vagotomy as well as bilateral stellate ganglionectomy merely raised the threshold for arrhythmia without affecting the blood pressure response. The neural supply to the heart, therefore, does not seem to be the major pathway concerned in the genesis of the centrogenic cardiovascular effects of aconitine. 4. The centrally evoked release of endogenous catecholamines from the adrenal glands was responsible for the aconitine-induced arrhythmia, since the arrhythmia could be blocked or prevented by prior reserpinization, bilateral adrenalectomy or thoracic splanchnic nerve section. 5. α- and β-adrenoceptive receptor blocking agents prevented or abolished the aconitine-induced arrhythmia in a manner similar to the catecholamine-induced arrhythmia.